Expansion of the distribution of romaleid grasshoppers (Orthoptera) of the Collection of the Paraense Emílio Goeldi Museum - BRAGA, CARLOS ELÍAS; NUNES-GUTJAHR, ANA LÚCIA (Revista Colombiana de Entomología, 2010)
The Invertebrate Collection of the Paraense Emílio Goeldi Museum (MPEG) is century-old and holds 494 specimens of Romaleidae grasshoppers. This work presents 11 species that constitute new records for Brazil, the Amazon Region and the Brazilian states of Acre, Mato Grosso, Pará and Tocantins.